2009
DOI: 10.1108/02651330910960780
|View full text |Cite
|
Sign up to set email alerts
|

Marketing in non‐profit organizations: an international perspective

Abstract: Purpose -This study tests three hypotheses: (1) that non-profit organizations follow a customer-centered approach to marketing, (2) that marketing is run by marketing-trained staff and (3) that cross-continental differences in the adoption of marketing in the UK, the USA and Australia exist due to differences in the operating environment. Methodology -A survey study was conducted with non-profit managers. The sample contains 136 respondents; 36 from the UK, 33 from the USA and 67 from Australia. Findings -Non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 29 publications
3
94
0
6
Order By: Relevance
“…Even though the general belief amongst marketing academicians is that the concept of marketing can be applied to NGO's, the numbers of persons who are skeptical about this idea have been on the increase since the beginning of 1990's (Başfırıncı, 2012). Conversely, it has been observed that the use of marketing tools applied in NGO's has not been as successful as that of profit organizations (Dolnicar and Lazarevski, 2009), because the non-governmental organizations are considerably different to commercial businesses in terms of their organizational structure, management and philosophy. The primary reason for these differences is that the main priority of NGO's in terms of their function is not to sell goods or services but to serve a mission (Başfırıncı, 2012).…”
Section: Marketing For Non-government Organizationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though the general belief amongst marketing academicians is that the concept of marketing can be applied to NGO's, the numbers of persons who are skeptical about this idea have been on the increase since the beginning of 1990's (Başfırıncı, 2012). Conversely, it has been observed that the use of marketing tools applied in NGO's has not been as successful as that of profit organizations (Dolnicar and Lazarevski, 2009), because the non-governmental organizations are considerably different to commercial businesses in terms of their organizational structure, management and philosophy. The primary reason for these differences is that the main priority of NGO's in terms of their function is not to sell goods or services but to serve a mission (Başfırıncı, 2012).…”
Section: Marketing For Non-government Organizationsmentioning
confidence: 99%
“…For that reason they require marketing for the purpose of survival, growth and strength in their contribution for general wealth. This is why this group is considered as the third sector (Dolnicar and Lazarevski, 2009). Additionally, for Kotler and Levy, marketing has the capacity to expand a smallscale business beyond its own role and this feature gives wider social meaning to the subject.…”
Section: Marketing For Non-government Organizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have proven a significant positive correlation between company success and a strong customer orientation [29]. Although market orientation (which implies a focus on a target audience) is a crucial aspect for successful marketing strategies for both for-profit and nonprofit enterprises, a study in the UK, the USA, and Australia revealed that nonprofits are still dominated by an organization-centered mindset in which marketing appears to be primarily defined by promotional activities [25,26]. However, what does target audience-centeredness mean for an organization?…”
Section: Phase I: Target Audience-centered Marketing In a Nonprofit Ementioning
confidence: 99%